2023
DOI: 10.3390/nu15020477
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity and Digestibility of Microalgae Tetraselmis sp. and Nannochloropsis sp. as Basis of Their Potential as Novel Functional Foods

Abstract: It is estimated that by 2050, the world’s population will exceed 10 billion people, which will lead to a deterioration in global food security. To avoid aggravating this problem, FAO and WHO have recommended dietary changes to reduce the intake of animal calories and increase the consumption of sustainable, nutrient-rich, and calorie-efficient products. Moreover, due to the worldwide rising incidence of non-communicable diseases and the demonstrated impact of diet on the risk of these disorders, the current es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 137 publications
0
6
0
Order By: Relevance
“…Isochrysis galbana , Nannochloropsis sp., Tetraselmis sp. and Phaeodactylum tricornutum are EPA‐producers, while Porphyridium cruentum is an ARA producer 57,58 . Furthermore, as largely reported by Spolaore et al ., 59 for the high content of B vitamins and phycobiliproteins these species are considered as healthy promoters with antioxidant, cholesterol‐lowering and other beneficial effects.…”
Section: Biotechnological Applicationsmentioning
confidence: 82%
See 1 more Smart Citation
“…Isochrysis galbana , Nannochloropsis sp., Tetraselmis sp. and Phaeodactylum tricornutum are EPA‐producers, while Porphyridium cruentum is an ARA producer 57,58 . Furthermore, as largely reported by Spolaore et al ., 59 for the high content of B vitamins and phycobiliproteins these species are considered as healthy promoters with antioxidant, cholesterol‐lowering and other beneficial effects.…”
Section: Biotechnological Applicationsmentioning
confidence: 82%
“…and Phaeodactylum tricornutum are EPA-producers, while Porphyridium cruentum is an ARA producer. 57,58 Furthermore, as largely reported by Spolaore et al, 59 for the high content of B vitamins and phycobiliproteins these species are considered as healthy promoters with antioxidant, cholesterol-lowering and other beneficial effects. Moreover, Arthrospira has gained significant popularity in the health and food industry, as primary food source in Asian countries, mainly in China, Korea, and Japan, while in other parts of the world it has been used as a nutrition supplement.…”
Section: Production Of Nutraceutical Compoundsmentioning
confidence: 84%
“…This may be due to the presence and antioxidant activity of lipophilic antioxidants as well as vitamin C found in the microalgae N.o. [ 41 , 113 ]. Previous data have shown that treatment of fibroblasts with ascorbic acid under conditions of UV-induced oxidative stress reduces the formation of lipid peroxidation products and their further interactions, including reducing the level of carbonyl groups and the amount of another oxidative product of proteins—dityrosine [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date no clinical trial has investigated the implications of microalgae antioxidant molecules on human metabolic health. Future research is also required to define the digestibility of microalgae and the bioavailability of the antioxidant molecules that they contain, in order to counteract oxidative stress and insulin resistance [ 119 , 121 ].…”
Section: Microalgae As a Source Of Nutraceuticalsmentioning
confidence: 99%